Numerical study of the flow structure and heat transfer in rotating cavity with and without jet - Kiełczewski, K.; Tuliszka-Sznitko, E. (Archives of Mechanics, 2013)
In the paper we investigate the flow with heat transfer in the rotating cavity of different geometrical parameters and different Reynolds numbers. We focus on the near-wall characteristics and compare our results with the experimental and numerical data published in literature as well as with the theoretical results. We also present the preliminary results obtained for rotor/rotor configurations with the axial annular jet. Computations are performed using pseudo-spectral methods. Parallelization of the DNS code allows us to perform computations on the meshes with up to 35 million collocation points.